DISKURSUS PEMIKIRAN KEAGAMAAN DI INDONESIA, STUDI KRITIS PEMIKIRAN MUHAMMADIYAH DAN NAHDATUL ULAMA - Hasyim Ashari; Mustari Mustafa; Muhaimin Latief (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2025)
This paper examines the discourse of the thoughts of two largest Islamic organizations in Indonesia, namely Muhammadiyah and Nahdlatul Ulama (NU), particularly in the aspects of theology and Sufism. The purpose of this study is to explain the background of the establishment of these two organizations and to describe their thoughts in theology and Sufism. The research uses a descriptive qualitative approach with a text analysis method. Data is collected from various sources, including books and articles published in academic journals that discuss Muhammadiyah and Nahdlatul Ulama (NU), starting from their background and thoughts. The results of this study are as follows: 1) Muhammadiyah was founded to purify and restore the purity of Islam, reformulate Islamic doctrine, reformulate Islamic education, and protect Islam from external threats. Meanwhile, the emergence of NU was influenced by the dynamics of the international Islamic world. 2) Muhammadiyah is considered to have a traditional approach in theology, even though it is not explicitly stated in its statutes. Meanwhile, NU explicitly states in its statutes that it follows the madhhab of Imam al-Ash'ari and al-Maturidi. 3) In Muhammadiyah’s teachings, elements of Sufism such as tazkiyat al-nafs and dhikr al-mawt are reflected. In contrast, NU firmly declares its adherence to the teachings of Imam al-Junaid al-Baghdadi and Imam al-Ghazali in Sufism. Keywords: Muhammadiyah, Nahdlatul Ulama, Theology, Sufism